The Significance of the South Pacific for Comparative Studies in Labour Law - Brooks, B T (Victoria University of Wellington Law Review, 1996)
In this article, Professor Brooks traces the introduction of labour law into the South Pacific island states and its development there. He considers the richness of the subject for interdisciplinary and comparative study, and indicates labour law as fertile ground for an investigation into the tensions in the Pacific states between tradition and modernisation.